2016
DOI: 10.1016/j.bbi.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Acute bouts of exercise induce a suppressive effect on lymphocyte proliferation in human subjects: A meta-analysis

Abstract: Evidence suggests lymphocyte proliferation is suppressed following acute bouts of exercise, with exercise lasting longer than one hour having a greater magnitude of effect regardless of exercise intensity. Variations in observed effect sizes across intensity, duration, and competitive environment further highlight our need to acknowledge the impact of study designs in advancing our understanding of exercise immunology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 60 publications
(40 reference statements)
0
26
0
3
Order By: Relevance
“…Fresh culture media was used as a negative control, and an NLX virus standard as a positive control in each reaction plate. An RT assay mix of H 2 0, 50 mmol/L Tris (pH 7.9), 75 mmol/L KCL, 2 nmol/L DTT, 0.1875 mmol/L ATP, 5 mmol/L MgCl 2 , RT Primer (25 mg/L), 0.05% NP‐40, 2 μ mol/L dTTP, and 2 µ Ci [ 32 P]‐ α ‐TTP was prepared and vortexed thoroughly (Siedlik et al ). 30 μ L of RT assay mix was added to each well and the plate was incubated at 37°C for 3 h. RT mix was added to Whatman paper in individual spots and allowed to dry.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fresh culture media was used as a negative control, and an NLX virus standard as a positive control in each reaction plate. An RT assay mix of H 2 0, 50 mmol/L Tris (pH 7.9), 75 mmol/L KCL, 2 nmol/L DTT, 0.1875 mmol/L ATP, 5 mmol/L MgCl 2 , RT Primer (25 mg/L), 0.05% NP‐40, 2 μ mol/L dTTP, and 2 µ Ci [ 32 P]‐ α ‐TTP was prepared and vortexed thoroughly (Siedlik et al ). 30 μ L of RT assay mix was added to each well and the plate was incubated at 37°C for 3 h. RT mix was added to Whatman paper in individual spots and allowed to dry.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that both aerobic and resistance exercise have the potential to alter the immune state of an individual. Evidence from a 2016 meta‐analytic review suggests the proliferative response of mixed lymphocyte populations (i.e., peripheral blood mononucleocytes (PBMCs)) to in vitro mitogenic stimuli is suppressed following an acute bout of exercise (Siedlik et al ). Notably, most of the research investigating the effect of exercise on immunity have focused on PBMC proliferation in response to an acute bout of aerobic exercise (Walsh et al ; ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conforme meta-análise, a diminuição da proliferação linfocitária após a prática de exercício de alta intensidade é bem documentada 7 . Os possíveis mecanismos envolvidos são a ação da epinefrina e do cortisol 19 .…”
Section: Discussionunclassified
“…Green et al 6 relatam que o exercício aeróbio sob condições agudas pode alterar a proliferação linfocitária. A capacidade proliferativa linfocitária pode ser usada em contextos clínicos para avaliar a função imune, mas sua resposta ao exercício físico de diferentes intensidades ainda não é bem esclarecida 7 . Estudar essa associação pode fornecer melhores evidências para a prescrição de exercício de forma benéfica e segura ao sistema imune 8 , vislumbrando seu uso como estratégia não farmacológica para aumento da imunidade e da contagem de determinadas populações linfocitárias, bem como uma forma de evitar diminuição no rendimento de atletas e infecções na população em geral 2,8 .…”
Section: Abstract: Lymphocyte; Exercise; Cell Proliferationunclassified